The Effect Of Audit Committee, Firm Value, Sales Growth And Firm Size On Tax Avoidance With Corporate Transparency As A Moderating Variable - Berkat Firman Lase (Green Publisher Indonesia, 2024)
This study is a development of research entitled The Effect of Company Size, Company Value, Sales Growht on Tax Avoidance with Corporate Transparency as a Moderating Variable. It tests the food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the period 2016 to 2021. Whereas in this study I will test the manufacturing sub-sector using the 2019 - 2022 financial report period. This study uses descriptive statistical analysis to describe data from 2012-2022, the objectives of this study are: To determine empirically the effect of the Audit Committee on tax avoidance, to determine empirically the effect of Company Value on tax avoidance, to determine empirically the effect of Sales Growth on tax avoidance, to determine empirically the effect of Firm Size on tax avoidance, to test the moderating effect of Corporate Transparency in the effect of the Audit Committee on tax avoidance, to test the moderating effect of Corporate Transparency in the effect of Company Value on tax avoidance, to test the moderating effect of Corporate Transparency in the effect of Sales Growth on tax avoidance, to test the moderating effect of Corporate Transparency in the effect of Firm Size on tax avoidance.